Analisis Faktor-Faktor Yang Mempengaruhi Penyerapan Tenaga Kerja Pada Sektor Pariwisata Di Provinsi Bali (2012-2021) - Ketut Widiasih; Ni Nyoman Yuliarmi (Universitas Dian Nuswantoro, 2022)
The economic development of a region or a country is basically the interaction of various groups of variables including human resources, natural resources, capital, technology and others. The location of this research was conducted in the Province of Bali. This location was chosen because the province of Bali is famous for its tourism sector compared to other provinces. In addition, there are still problems regarding employment in the tourism sector, which continues to decline every year. This study uses data on the number of tourist arrivals visiting Bali Province in 2012-2021, hotel occupancy rates, and minimum wages in Bali province in 2012-2021 sourced from BPS Bali Province in 2021, and data on the number of tourist objects sourced from the Bali Province Tourism. This study uses panel data with a five-year time series from 2012-2021 and cross-sectional data for 9 regencies/cities in Bali Province. The results of the analysis show that the number of tourist visits, hotel occupancy rates, number of tourist objects, and the minimum wage simultaneously affect employment in the province of Bali. The number of tourist visits has a positive effect on employment, while the hotel occupancy rate, number of tourist objects, and the minimum wage partially have no positive and significant effect on employment in the Province of Bali.